Independent scout general proficiency requirement (SKU) examination: An autonomy-based assessment for developing students’ independence and discipline - Mohamad Yusuf Wisnu Wardana; Dinda Ika Putri Yuniar; Mar'atus Sholikhah; Bagus Dwi Permana; Abdul Saidullah; Susi Hermin Rusmiati (EDUCARE Journal of Primary Education, 2026)
Strengthening Character Education in elementary schools still faces operational challenges, as the values of independence and discipline are often taught normatively rather than developed through direct, structured, repeated, and consistently measurable experiences. This study aims to analyze the implementation of the Independent Scout General Proficiency Requirement (SKU) Examination based on limited assistance in fostering independent initiative and habituating disciplined behavior among Cub Scout students in elementary schools. This research employed an intrinsic qualitative case study at SD Hangtuah 11 Surabaya, using purposive sampling, interviews, observation, documentation, thematic analysis, triangulation, member checking, and ethical research procedures. The findings reveal that: 1) the Independent SKU Examination develops students’ independence through the initiative to approach the Scout coach, competency demonstrations without direct guidance, and limited assistance that strengthens responsibility, courage, and learning control; and 2) Scout habituation instills discipline through weekly routines, roll calls, uniform-attribute checks, task evaluation, punctuality, and orderliness, enabling students to gradually develop self-control and procedural compliance. This study concludes that the Independent Scout SKU Examination is not merely an assessment instrument, but a pedagogical practice that develops students’ independence and disciplined character through autonomy, limited assistance, and routine habituation to counterbalance the culture of instant gratification. The study contributes to Self-Determination Theory by elaborating the concepts of autonomy support, limited assistance, and pedagogical distancing, while also offering a structured character assessment model for the sustainable development of independence and discipline among elementary school students.